2019
DOI: 10.1017/s002221511900104x
|View full text |Cite
|
Sign up to set email alerts
|

Do central vestibular findings predict abnormal findings on magnetic resonance imaging?

Abstract: ObjectiveTo determine whether central findings from vestibular tests predict abnormal findings on magnetic resonance imaging.MethodThis study was a retrospective case series at a tertiary referral centre. The main outcome measure of this diagnostic intervention study was the positive predictive value of central vestibular findings in relation to magnetic resonance imaging abnormalities.ResultsCentral vestibular findings had a 50.9 per cent positive predictive value for magnetic resonance imaging abnormalities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
1
1
0
Order By: Relevance
“…Furthermore, this study showed that oculomotor tests, regardless of rater, had only moderate sensitivity (50-70%) and specificity (40-70%) for predicting central lesions on MRI, in line with previous findings [14,15,19]. Interestingly, both raters showed low PPV but high NPV, suggesting the necessity of imaging studies if clinicians cannot confidently exclude central vestibular disorder.…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, this study showed that oculomotor tests, regardless of rater, had only moderate sensitivity (50-70%) and specificity (40-70%) for predicting central lesions on MRI, in line with previous findings [14,15,19]. Interestingly, both raters showed low PPV but high NPV, suggesting the necessity of imaging studies if clinicians cannot confidently exclude central vestibular disorder.…”
Section: Discussionsupporting
confidence: 89%
“…This contrasts with Mankekar et al . 47 who reported a 50.9 per cent positive predictive value for abnormal MRI in patients with central vestibular pathology. Such discrepancy may be attributable to our small cohort of patients with central causes (20.8 per cent, n = 21) or our small numbers of patients referred for further imaging following their initial specialist clinic appointment (6.9 per cent, n = 7).…”
Section: Discussionmentioning
confidence: 99%